Selective MPP+ uptake into synaptic dopamine vesicles: possible involvement in MPTP neurotoxicity. - Del Zompo, M. (Nature Publishing Group, 1993)
1. In the present study we provide evidence for a saturable, Mg2+/ATP- and temperature-dependent, tetrabenazine-, dopamine-, and amphetamine-sensitive uptake of 1-methyl-4-phenylpyridinium ion (MPP+) in synaptic vesicles from mouse striatum. 2. Similarity in the properties of the vesicular uptake suggests that in the striatum dopamine and MPP+ share the vesicular carrier. 3. The presence of MPP+ vesicular uptake in dopamine-rich regions such as striatum, olfactory, tubercles and hypothalamus, as well as its absence in cerebellum, cortex and pons-medulla, suggest that monoamine vesicular carriers differ between highly and poorly dopamine-innervated regions. 4. The restriction of active MPP+ uptake to the dopaminergic regions, which reflects the previously shown distribution of [3H]-MPP+ binding sites in mouse brain membranes, indicates MPP+ as a marker of the vesicular carrier for dopamine in dopaminergic neurones. 5. A role in MPP+ neurotoxicity is suggested for this region-specific, vesicular storage of the toxin.